Fast computation of accessibility cones for assisting 3 + 2 axis milling. Issue 5 (3rd September 2018) - Inui, Masatomo; Nagano, Shinji; Umezu, Nobuyuki
ABSTRACT: In this paper, we propose an algorithm for computing all appropriate cutter postures in the 3 + 2 axis milling of the mold part. As a measure of the appropriateness of the cutter posture, the peak angle of the accessibility cone (AC) is used. We use the polygon rendering function of the graphics processing unit for computing the AC. In this method, the necessary cost in the computation is basically proportional to the number of polygons to render in generating an image of the offset shape. A novel technology named "visible surface offsetting" is developed for reducing the rendering cost of the offset shape. An experimental system is implemented and some computation results are demonstrated. Our system can determine the cutter postures appropriate for 3 + 2 axis milling of the mold part in a few minutes. GRAPHICAL ABSTRACT: